TEM sample preparation of a SEM cross section using electron beam induced deposition of carbon. Issue 9 (August 2015) - Ricci, E.; Cazzaniga, F.; Testai, S.
Abstract: In this paper we describe a method to prepare a Transmission Electron Microscopy (TEM) lamella with a Focus Ion Beam-Scanning Electron Microscope (FIB-SEM), starting from a SEM cross section. If the structure of interest is already cut, it's important to protect this area from the damages induced by the other steps of the lamella preparation. For this purpose an Electron Beam Induced Deposition (EBID) of carbon is used; a full TEM characterization of the carbon deposited is done to evaluate the influence of the EBID of carbon on the TEM analysis. Some examples and results are presented. Highlights: Methodology for preparing a TEM lamella with FIB-SEM, starting from a SEM sample Protect the structure of interest with EBID of Carbon TEM characterization of EBID of Carbon